Ethnic minorities and nation-building in the post-Soviet space: Constructing a theoretical framework - I. Kudryashova; E. Meleshkina (Vestnik MGIMO-Universiteta)
Divisions over recognition of Kosovo, Abkhazia and South Ossetia’s independence put in focus policies towards ethnic minorities, structuring and legitimization of power in newly-formed multi-ethnic states. In most cases state-building requires the homogenization of population, i.e. “nationalizing” policies of both exclusion and inclusion. The relevant European experience has been conceptualized by political scientists examining the key parameters of “nationalizing” policies used in respect of ethnic minorities as well as the influence of centre-periphery polarity and different ways of political control maintenance on the process of state- and nation-building. Applying these approaches to the post-Soviet realities the authors offer a theoretical framework for analyzing grounds, forms and consequences of the politicization of ethnicity and evaluation of possible stability/instability, including secessions, bringing a realistic perspective to bear on what is happening and what can be done.